IFPRI’s COVID-19 Policy Response Portal: Identifying trends and implications for food systems - Resnick, Danielle (International Food Policy Research Institute, 2020)
Developing countries have employed a wide range of policies to control COVID-19 and relieve economic stress. These responses continue to evolve, and different actions targeting the same problem vary widely in approach and impact. For instance, to maintain food supplies, some countries have provided direct support to farmers, some have imposed food export bans, and some do both. In addition, many responses overlap and interact, so their cumulative impacts can be difficult to interpret in isolation. For example, borders may be kept open for transporting food, but stringent screening and quarantine measures may create significant delays that deter truckers from making the trip. Providing inputs to farmers may do little for food accessibility if markets are shut down or have severely limited operating hours.